(untitled) (Journal of Bangladesh Academy of Sciences, 2014)
The effects of Li2O additives on the structural, magnetic and electrical properties of Ni0.5Mg0.5Fe2O4, prepared by conventional double sintering ceramic technique were investigated. The X-raydiffraction (XRD) pattern of the prepared samples showed single phase cubic spinel structure.Variation of lattice parameter has been observed with the variation of Li2O content. Theenhancement of bulk density has been observed for 2 mol% Li2O additive, but further increase inLi2O concentration, these values decrease. Enhancement of initial permeability (??) have beenobserved for the sample with 2 mol% Li2O additives while it decreases for higher concentration ofLi2O. The Curie temperature is found to decrease with the increase in Li2O additive. The resistivityincreases with increasing additive content and showed a significant dispersion with frequency,which is the normal ferromagnetic behavior. The dielectric constant (??) measurement showed thenormal dielectric behavior of spinel ferrite. Possible explanation for the observed features arediscussed. DOI: http://dx.doi.org/10.3329/jbas.v38i1.20198 Journal of Bangladesh Academy of Sciences, Vol. 38, No. 1, 7-18, 2014